Catechol-based chemistry for hypoglycemia-responsive delivery of zinc-glucagon via hydrogel-based microneedle patch technology - Amin GhavamiNejad; Jackie Fule Liu; Sako Mirzaie; Brian Lu; Melisa Samarikhalaj; Adria Giacca; Xiao Yu Wu (Nature Communications)
Abstract Hypoglycemia is a serious and potentially life-threatening condition for people with insulin-dependent diabetes. To provide a safeguard against hypoglycemia, we introduce a “smart” microneedle (MN) patch that senses glucose levels and delivers a blood glucose-raising agent (Zinc-Glucagon (Z-GCN)) in response to hypoglycemia. Herein, we describe the use of catechol and boronic acid chemistry to design a self-crosslinkable hydrogel-based MN that stimulates the release of Z-GCN during hypoglycemia. In this design, the catechol groups bind to Z-GCN through metal-ligand complexation. At hyperglycemia, boronic acids react with glucose to generate cyclic boronate esters. As the glucose concentration decreases, the boronic acid groups dissociate and are favored over Z-GCN in binding with catechol, which promotes the release of Z-GCN. We fully characterize the fabricated MN in vitro. Moreover, we further evaluate the MN and demonstrate the in vivo glucose-responsive delivery of Z-GCN from the patch. We also show its effectiveness in preventing hypoglycemia for up to 6 h in type 1 diabetic male rats against two consecutive insulin overdose challenges. Since many proteins/peptides have a high binding affinity to metal ions, the introduced mechanism driven by the competitive binding of catechol-metal ions has great implications in drug delivery applications of various protein/peptide-based therapeutics.